PENGARUH RASIO KEUANGAN TERHADAP PERTUMBUHAN LABA PERUSAHAAN (Studi Empiris pada Perusahaan Konstruksi, Properti, dan Real Estate yang Terdaftar Konsisten di Bursa Efek Indonesia Tahun 2018-2021) - Anisa Setyaningdiyah; Agustinus Santosa Adiwibowo (Diponegoro Journal of Accounting, 2023)
This study aims to analyze the effect of current ratio, debt to asset ratio, net profit margin, return on assets, and return on equity on profit growth. The population in this study were all companies  on  construction,  property,  and  real estate sector  listed  in Indonesia  Stock Exchange Database for the year 2018 to 2021. The sampling methode used in this research was purposive sampling. Total number of samples used in this study were 96 study samples. The data used in this study were obtained from Bloomberg Database. The data in this study were analyzed using panel data regression techniques. The result of this study indicate that current ratio and return on assets has positive effect on profit growth. While, debt to assets ratio, net profit margin, and return on equity has no effect on profit growth.